The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra07203a
|View full text |Cite
|
Sign up to set email alerts
|

FeII-catalysed insertion reaction of α-diazocarbonyls into X–H bonds (X = Si, S, N, and O) in dimethyl carbonate as a suitable solvent alternative

Abstract: The insertion reaction of a broad range of diazo compounds into Si–H bonds was found to be efficiently catalysed by Fe(OTf)2 in an emerging green solvent i.e. dimethyl carbonate (DMC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…dimethyl carbonate (DMC) (Scheme 19). [39] After the optimization of the reaction conditions, different diazo compounds and silane moieties were explored to extend the substrate scope. It was seen that among the tested diazo compounds the higher yields were obtained for diazo compounds having electron‐withdrawing groups either on the para‐ or ortho ‐position of aryl moiety.…”
Section: Iron‐based Chemical Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…dimethyl carbonate (DMC) (Scheme 19). [39] After the optimization of the reaction conditions, different diazo compounds and silane moieties were explored to extend the substrate scope. It was seen that among the tested diazo compounds the higher yields were obtained for diazo compounds having electron‐withdrawing groups either on the para‐ or ortho ‐position of aryl moiety.…”
Section: Iron‐based Chemical Catalystsmentioning
confidence: 99%
“…In addition of other carbene insertion reactions, Ollevier and group members studied the Fe(OTf) 2 catalyzed insertion of aliphatic and aromatic amines (83) into methyl α‐phenyl‐α‐diazoacetate (21) (Scheme 28). [39] They observed that primary aromatic amines gave high yield of desired products with no side reactions, however, reaction required prolonged time to get complete in case of secondary aromatic amines.…”
Section: Iron‐based Chemical Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the Ollevier group continued their study on iron-catalyzed Si-H insertions while opting for a greener solvent alternative to replace the commonly required dichloromethane (DCM). 29 They found that dimethyl carbonate (DMC) could be used for an Fe(OTf) 2 -catalyzed insertion reaction of -diazo compounds which proceeds in high yields (up to 98%) for a wide scope of diazo compounds and silanes. The reaction mechanism of this iron-catalyzed Si-H insertion was further examined.…”
Section: Short Review Synthesis 22 Insertion Into Si-h Bondsmentioning
confidence: 99%
“…Also, the Ollevier group reported Fe(OTf) 2 -mediated mono N-H insertions of methyl -diazo--phenylacetate with various primary and secondary amines. 29…”
Section: Short Review Synthesismentioning
confidence: 99%